Moderate intensity and volume downhill run does not impair knee joint stability at early and late phases of quadriceps/hamstrings contraction - Assumpcao, Claudio de Oliveira [UNESP]; Rabello de Lima, Leonardo Coelho [UNESP]; Dias de Oliveira, Felipe Bruno [UNESP]; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sergio [UNESP] (Ios Press, 2014)
BACKGROUND AND OBJECTIVE: Muscle strength imbalance can be an important factor in hamstrings muscle strain. The main purpose of this study was to investigate the effects of downhill running on hamstrings/quadriceps torque (H/Q(torque)) and the electromechanical delay (H/Q(EMD)) ratios.METHODS: Fifteen active male individuals performed two maximal voluntary isometric contractions of the knee extensors and knee flexors, from which the maximal muscle torque, EMD and H/Q(torque) and H/Q(EMD) ratios were extracted. Thereafter, the participants performed a 30-minute downhill run (-16%) at 70% VO(2)max. Dependent variables were assessed immediately before, immediately following and 48 hours after the effort.RESULTS: Maximal isometric torque decreased significantly immediately after the downhill run for both the extensors (pre: 271.8 +/- 45.9 N.m; post: 235.5 +/- 55.7 N.m) and flexors (pre: 112.2 +/- 26.3 N.m; post: 97.7 +/- 27.2 N.m). No significant difference was identified over time for the EMD of the vastus lateralis and biceps femoris muscles. The H/Q(torque) and H/Q(EMD) ratios were not influenced by the downhill run.CONCLUSION: We have demonstrated that moderate intensity and volume downhill run does not impair knee joint stability at early (H/Q(EMD)) and late phases (H/Q(torque)) of quadriceps/hamstrings contraction.
Keywords: Strength; fatigue; muscle damage